Effect of Mesoscale Ordering on the Density of States of Polymeric Semiconductors. Issue 11 (10th March 2015) - Gemünden, Patrick; Poelking, Carl; Kremer, Kurt; Daoulas, Kostas; Andrienko, Denis; Char, K.; Zentel, R.
<x xml:space="preserve">Abstract</x> A multiscale simulation scheme, which incorporates both long‐range conformational disorder and local molecular ordering, is proposed for predicting large‐scale morphologies and charge transport properties of polymeric semiconductors. Using poly(3‐hexylthiophene) as an example, it is illustrated how the energy landscape and its spatial correlations evolve with increasing degree of structural order in mesophases with amorphous, uniaxial, and biaxial nematic ordering. It is shown that the formation of low‐lying energy states in more ordered systems is mostly due to larger (on average) conjugation lengths and not due to electrostatic interactions. The proposed scheme is general and can be applied to a wide range of polymeric organic materials.